KARAKTERISASI TIGA GALUR HARAPAN HASIL PERSILANGAN PADI GOGO LOKAL BENGKULU PADA BUDIDAYA ORGANIK DAN ANORGANIK - Asfaruddin Asfaruddin; Sri Mulatsih (University of Prof. Dr. Hazairin, SH, 2020)
This research was conducted to determine the character of hope lines in organic and inorganic cultivation. The study used a split plot design with three replications. As the main plot is the type of fertilizer with two level of organic fertilizer, complete fertilizer (organic + an organic) and organic fertilizer. As subplots were lines from Bengkulu local upland rice with three levels namely UNHZ 12, UNHZ 24 and UNHZ 31. The results showed that the type of fertilizer significantly affected plant height, number of productive tillers, panicle length, grain weight of 100 grains, and weight of grain per clump, but has no significant effect on the age of flowering, harvest age, and grain per panicle. The strain has a very significant effect on the number of productive tillers, flowering age, harvest age, panicle length, grain per panicle and grain weight of 100 grains. The interaction of fertilizers and strains has a very significant effect on panicle length, and the weight of 100 grains, significantly influences the number of panicle grains, has no significant effect on plant height, number of productive tillers, flowering age, harvest age, and grain weight per clump.